2023
DOI: 10.1186/s12957-022-02836-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic and therapeutic biomarkers in type 2 papillary renal cell carcinoma

Abstract: Background Papillary renal cell carcinoma (PRCC) can be divided into type 1 (PRCC1) and type 2 (PRCC2) and PRCC2 share a more invasive phenotype and worse prognosis. This study aims to identify potential prognostic and therapeutic biomarkers in PRCC2. Methods A cohort from The Cancer Genome Atlas and two datasets from Gene Expression Omnibus were examined. Common differentially expressed genes (DEGs) were screened and potential biomarkers were explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This is consistent with the results of a previous study. [ 30 ] Subsequently, we constructed a line column predicting the 1-, 3-, and 5-year survival rates of patients with KIRP, and the results were encouraging. In addition, we conducted univariate and multivariate analyses of factors influencing KIRP prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of a previous study. [ 30 ] Subsequently, we constructed a line column predicting the 1-, 3-, and 5-year survival rates of patients with KIRP, and the results were encouraging. In addition, we conducted univariate and multivariate analyses of factors influencing KIRP prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of a previous study. [30] Subsequently, we constructed a line column The data was downloaded from the HPA database(https://www.proteinatlas.org/). The expression of CCNB1 was evaluated according to the intensity of the staining (0, 1+, 2+, and 3+) and the percentage of positive cells, which was scored as 0 (0%), 1 (1-25%), 2 (26-50%), 3 (51-75%) or 4 (76-100%).…”
Section: Discussionmentioning
confidence: 99%
“…These divisions largely represent differences in invasiveness and cost. Similarly, the biomarkers can also be thought of as single factor (IL-6 level, PDL-1 status), composite easily interpretable scores (Heng score, MSKCC score, Motzer score) and composite difficult to interpret scores (NGS biomarkers derived from PCA or machine learning) [42][43][44][45][46][47][48][49]. As these biomarkers develop, it will be important to consider both the ease with which they can be collected as well as their known relationship to drug or tumorigenesis/invasive pathways.…”
Section: Discussion/future Directionsmentioning
confidence: 99%
“…In order to explore the interaction between CCNB1 and other genes, we established a co-expression analysis circle, in which TPX2, KIF20A, KIF11, CDK1, PBK, and KIFC1 showed the strongest positive correlation with CCNB1. A study has reported higher expression level of TPX2 was signi cantly associated with worse overall survival in Papillary renal cell carcinoma [31]. In another research, KIF20A knockdown can inhibit the proliferation and invasion of two kinds of renal carcinoma cell lines to a certain extent [32].…”
Section: Drug Sensitivity Screening and Molecular Dockingmentioning
confidence: 95%